A comparative study of glutamate oxaloacetate transaminase (GOT) and glutamate pyruvate transaminase (GPT) levels in the saliva of diabetic and normal patients. (October 2014) - Verma, M; Metgud, R; Madhusudan, AS; Verma, N; Saxena, M; Soni, A
Abstract Diabetes has been reported to affect salivary glands adversely in humans and experimental models. Glutamate oxaloacetate transaminase (GOT), glutamate pyruvate transaminase (GPT) and lactate dehydrogenase (LDH) are salivary enzymes that also are widely distributed in animal tissues. We determined GOT and GPT levels in saliva samples of 100 type 1 and 30 type 2 diabetic patients using reflectance spectrophotometry and compared them to 30 age and sex matched healthy controls. Statistically significant differences were observed in the mean values of GOT and GPT in type 1 diabetics compared to type 2 and control groups. Significantly higher GOT levels were found in the 1–20 year age group of type 1 diabetics. Our findings suggest that salivary gland damage is due to the same immunological attack that affects pancreatic β cells and results in type 1 diabetes.